Neotype designation for Calotes versicolor Daudin, 1802 (Sauria: Agamidae) with notes on its systematics - Gowande, Gaurang; Mishra, Anurag; Mirza, Zeeshan A. (Zootaxa, 2016)
Calotes versicolor Daudin, 1802 is one of the most widespread agamid lizard species which was described without a locality. The type specimen of the species has long been considered lost; however most workers considered Pondicherry as the type locality for the species. Studies by Zug et al. 2006 confirmed that C. versicolor is a complex of multiple species which necessitates fixing type locality and specimen for the species in order to resolve the systematics of the species complex. An adult male from Pondicherry was collected and is here designated as the neotype. A re-description of the species is provided along with notes on systematics of the species.